2011
DOI: 10.1017/s1743921312005145
|View full text |Cite
|
Sign up to set email alerts
|

Flares and habitability

Abstract: Abstract. At present, dwarf M stars are being considered as potential hosts for habitable planets. However, an important fraction of these stars are flare stars, which among other kind of radiation, emit large amounts of UV radiation during flares, and it is unknown how this events can affect life, since biological systems are particularly vulnerable to UV. In this work we evaluate a well known dMe star, EV Lacertae (GJ 873) as a potential host for the emergence and evolution of life, focusing on the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…High energy processes, including those that produce radio emission, are an important diagnostic of stellar magnetospheres and the influence of those magnetospheres on accretion, planet formation, and even habitability (Feigelson & Montmerle 1999;Feigelson et al 2002;Güdel 2002;Abrevaya et al 2012;Osten & Wolk 2015). Of the thousands of known exoplanets, hot Jupiters represent the best opportunity to study the interaction between star and exoplanet due to the close proximity, which creates amplified stellar wind flux and potentially an enhanced exoplanet magnetosphere that could stimulate strong radio emission such as that seen in Jovian decametric bursts (Zarka et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…High energy processes, including those that produce radio emission, are an important diagnostic of stellar magnetospheres and the influence of those magnetospheres on accretion, planet formation, and even habitability (Feigelson & Montmerle 1999;Feigelson et al 2002;Güdel 2002;Abrevaya et al 2012;Osten & Wolk 2015). Of the thousands of known exoplanets, hot Jupiters represent the best opportunity to study the interaction between star and exoplanet due to the close proximity, which creates amplified stellar wind flux and potentially an enhanced exoplanet magnetosphere that could stimulate strong radio emission such as that seen in Jovian decametric bursts (Zarka et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The probability of survival of radiation-tolerant microorganisms (halophilic archaea) was evaluated considering flare activity from the dM star EV-Lacertae (EV Lac, Gliese 873, HIP 112460) taking the UVC region (254 nm). Microorganisms survived the exposure to irradiation conditions (Abrevaya et al, 2011a). The same UV-resistant profiles were observed in experiments simulating radiation of the interplanetary environment or exposed in the low Earth orbit, where microorganisms have been exposed to EUV (e.g., Mancinelli et al, 1998;Abrevaya et al, 2011b;Mancinelli, 2015).…”
Section: Direct Effectsmentioning
confidence: 55%
“…Many of the tested organisms survived Mars-like conditions, where the best survival was presented by such organisms that have salt ability and tolerance at very dry locations. Salt tolerance might be important on Mars based on the liquids which could contain elevated concentration of salts (Tosca et al 2008;Altheide et al 2009;Mohlmann & Thomsen 2011), and salt-tolerant organisms found among the most durable extremofiles (Abrevaya et al 2008(Abrevaya et al , 2011. High survival was presented by Tolypothrix, Gloeocapsopsis and Symploca sp.…”
Section: Resultsmentioning
confidence: 99%